The integrated effects of leader–member exchange social comparison on job performance and OCB in the Chinese context - Yang, Chunjiang; Chen, Yashuo; Chen, Aobo; Ahmed, Syed Jameel (Frontiers in Psychology, 2023)
Although it has been long recognized that leader–member exchange social comparison (LMXSC) has critical implications for employee productivity, little attention has been given to systematically exploring the effects of LMXSC on employee performance in a specific cultural context. Integrating social exchange theory with social comparison theory, we examine a dual process model to explain how and when LMXSC affects employee performance outcomes in the Chinese context. Results based on multiphase, multisource data from China revealed that the mediating roles of employees’ perceived obligation toward the leader and self-esteem are examined simultaneously in the relationship between LMXSC and job performance and organizational citizenship behavior (OCB). Additionally, guanxi strengthens the connection between LMXSC and perceived obligation, while Zhongyong thinking erodes the connection between LMXSC and self-esteem. Taken together, these findings enhance our understanding of LMXSC in China.